2018
DOI: 10.3390/ijms19061629
|View full text |Cite
|
Sign up to set email alerts
|

Furosine Induced Apoptosis by the Regulation of STAT1/STAT2 and UBA7/UBE2L6 Genes in HepG2 Cells

Abstract: As a typical product in the Miallard reaction, research on the quantitative detection of furosine is abundant, while its bioactivities and toxic effects are still unclear. Our own work recently demonstrated the induction of furosine on apoptosis in HepG2 cells, while the related mechanism remained elusive. In this study, the effects of furosine on cell viability and apoptosis were detected to select the proper dosage, and transcriptomics detection and data analysis were performed to screen out the special gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…STAT1 (signal transducer and activator of transcription 1) is a key member of the mammalian STAT family and transduces signals from the cytoplasm to the nucleus for regulating gene expression [17]. Current research indicates that STAT1 has inhibitory effects on a variety of tumors such as colon (rectal) cancer [18], HCC [19,20], soft tissue sarcoma, pancreatic cancer, esophageal cancer, and metastatic melanomas [2124]. STAT1 not only inhibits tumorigenesis but also inhibits tumor cell proliferation, promotes apoptosis, inhibits angiogenesis, and regulates tumor immunity [24].…”
Section: Introductionmentioning
confidence: 99%
“…STAT1 (signal transducer and activator of transcription 1) is a key member of the mammalian STAT family and transduces signals from the cytoplasm to the nucleus for regulating gene expression [17]. Current research indicates that STAT1 has inhibitory effects on a variety of tumors such as colon (rectal) cancer [18], HCC [19,20], soft tissue sarcoma, pancreatic cancer, esophageal cancer, and metastatic melanomas [2124]. STAT1 not only inhibits tumorigenesis but also inhibits tumor cell proliferation, promotes apoptosis, inhibits angiogenesis, and regulates tumor immunity [24].…”
Section: Introductionmentioning
confidence: 99%
“…This PPI network diagram was used to reveal the central genes involved in the apoptosis of DEFs ( Figure 8 ). Genes with higher edge count, such as IL-6 [ 47 ], STAT1 [ 48 ], TNFAIP3 [ 49 ], CFLAR [ 50 ], IRF1 [ 51 ] and PTGS2 [ 52 ], may be the central nodes of the apoptotic network.…”
Section: Resultsmentioning
confidence: 99%
“…In several studies, the PI3K/AKT/ERK1/2 pathway has been shown to induce endothelial cell activation, proliferation, and migration [32,33,34], and this pathway has conflicting biological effects in organisms. On the one hand, the PI3K/AKT/ERK1/2 pathway acts as a positive feedback signal in protecting vascular endothelial cells from endogenous damage because it can promote their proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification was performed with 15 cycles and the quality of the products was examined with the Bioanalyzer 2100 System (Agilent, Santa Clara, CA, USA) and a Qubit™ 3 Fluorometer (Thermo Fisher). The libraries were then sequenced on the Illumina HiSeq platform () [34], and the data were exported to Excel spreadsheets with Simca-P for a principle components analysis (PCA), partial least squares discriminant analysis (PLS-DA), t -test, and variable importance in projection (VIP) plot analysis [34]. The differentially expressed genes between control and lactoferrin-treated groups were identified by the following criteria: (1) p -value < 0.05 ( t -test); (2) absolute fold change > 2.0.…”
Section: Methodsmentioning
confidence: 99%